The Frontier Gandhi : His Place in History - Korejo, M. S. (Karachi Oxford University Press, 1993)
On the life of Abdul Ghaffar Khan, 1891-1988, prominent Pushtun political leader.
Include Glossary and Index
Keywords: Pakistan -- India -- Politics and government -- Nationalists